Clinical Outcomes and Risk Factors for Graft Failure After Deep Anterior Lamellar Keratoplasty and Penetrating Keratoplasty for Macular Corneal Dystrophy. Issue 2 (February 2015) - Reddy, Jagadesh C.; Murthy, Somasheila I.; Vaddavalli, Pravin K.; Garg, Prashant; Ramappa, Muralidhar; Chaurasia, Sunita; Rathi, Varsha; Sangwan, Virender S.
Abstract : Purpose: The aim of this study was to compare visual acuity, clinical outcomes, complications, and risk factors for graft failure after deep anterior lamellar keratoplasty (DALK) and penetrating keratoplasty (PK) for macular corneal dystrophy. Methods: Retrospective comparative case series. Results: The PK group consisted of 109 eyes of 84 patients and the DALK group consisted of 21 eyes of 20 patients. The mean logarithm of the minimum angle of resolution best-corrected visual acuity at 3 and 12 months was 0.5 versus 0.5 ( P = 0.285) and 0.4 versus 0.4 ( P = 0.67) in the DALK and PK groups, respectively. There was no significant statistical difference in astigmatism and spherical equivalent between the 2 groups at 12 months. In the PK group, graft rejection that was the most common cause of graft failure was seen in 27 eyes (25%), of which 55% occurred within 1 year. In the DALK group, Descemet membrane microperforation occurred in 5 eyes (24%) intraoperatively, and early postoperative Descemet membrane detachment with double anterior chamber occurred in 9 eyes (43%). Kaplan–Meier estimate of graft survival in PK versus DALK groups were 93% versus 80% at 1 year and 78% versus 70% at 4 years, respectively. Conclusions: Visual and refractive outcomes are comparable between DALK and PK groups. DALK was superior to PK in its safety against postoperative complications such as endothelial rejection and secondary glaucoma. Graft failure in DALK was mostly associated with either intraoperative or early postoperative complications. DALK is a viable surgical option in cases with macular corneal dystrophy.